1999
DOI: 10.1046/j.1365-2958.1999.01176.x
|View full text |Cite
|
Sign up to set email alerts
|

The structural and functional organization of H‐NS‐like proteins is evolutionarily conserved in Gram‐negative bacteria

Abstract: SummaryThe structural gene of the H-NS protein, a global regulator of bacterial metabolism, has been identified in the group of enterobacteria as well as in closely related bacteria, such as Erwinia chrysanthemi and Haemophilus influenzae. Isolated outside these groups, the BpH3 protein of Bordetella pertussis exhibits a low amino acid conservation with H-NS, particularly in the N-terminal domain. To obtain information on the structure, function and/or evolution of H-NS, we searched for other H-NS-related prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
119
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(126 citation statements)
references
References 55 publications
7
119
0
Order By: Relevance
“…jouy.inra.fr), this domain was predicted to share the same three-dimensional structure as the E. coli H-NS C-domain resolved previously by NMR (Shindo et al, 1995). Finally, the expression of the strain Y1000 protein structural gene in an E. coli mutant fully reversed additional hns-related phenotypes, for example, the loss of motility on semi-solid medium and the ability to use b-glucoside as a sole carbon source, as observed previously with other H-NS-like proteins (Goyard & Bertin, 1997;Bertin et al, 1999Bertin et al, , 2001Tendeng et al, 2000). This strongly suggests that the protein we characterized belongs to the H-NS family and shares the same structural and functional organization as members of this family despite the unusually low amino acid conservation.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…jouy.inra.fr), this domain was predicted to share the same three-dimensional structure as the E. coli H-NS C-domain resolved previously by NMR (Shindo et al, 1995). Finally, the expression of the strain Y1000 protein structural gene in an E. coli mutant fully reversed additional hns-related phenotypes, for example, the loss of motility on semi-solid medium and the ability to use b-glucoside as a sole carbon source, as observed previously with other H-NS-like proteins (Goyard & Bertin, 1997;Bertin et al, 1999Bertin et al, , 2001Tendeng et al, 2000). This strongly suggests that the protein we characterized belongs to the H-NS family and shares the same structural and functional organization as members of this family despite the unusually low amino acid conservation.…”
supporting
confidence: 71%
“…Except for enterobacteria, where H-NS has been shown to control the expression of many genes, for example, in E. coli , the role in bacterial physiology of most H-NS-related proteins remains unknown. However, they constitute a family of proteins displaying an evolutionarily conserved structural and functional organization in two modules (Dorman et al, 1999;Bertin et al, 1999). The N-terminal oligomerization domain displays strong amino acid sequence divergence but is predicted to adopt an a-helix structure in all H-NS proteins , consistent with the recent three-dimensional structure of this domain in H-NS of E. coli (Renzoni et al, 2001;Bloch et al, 2003).…”
supporting
confidence: 54%
“…Despite the functional similarity between E. coli and S. marcescens H-NS, the mechanism by which H-NS modulates S. marcescens hemolysin is not clear. Previous studies have shown that H-NS can alter DNA supercoiling and that variation of DNA supercoiling may modulate expression of virulence genes in response to the same environmental factors (17). We have shown that environmental factors such as pH, osmolarity and growth phase affect hemolysin expression in hns mutants and in wild-type strains.…”
Section: Discussionmentioning
confidence: 74%
“…Our data also suggest that E. coli H-NS may also be involved in the regulation of the S. marcescens hemolysin operon. This finding is not surprising since the sequence of E. coli H-NS and S. marcescens H-NS appears to be highly conserved (17). Despite the functional similarity between E. coli and S. marcescens H-NS, the mechanism by which H-NS modulates S. marcescens hemolysin is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation